Darurat Judi Online, Menjerat Masyarakat di Era Digital - Aguk Nugroho; Vivin Astharyna Harysart; Nur Aziz; Marwan Marwan; M. Fikri Jauhari (Pusat Riset dan Inovasi Nasional, 2025)
The rapid advancement of information technology has brought about new challenges for society, one of which is the widespread practice of online gambling. With unrestricted access across time and space, online gambling is easily accessible through mobile devices and the internet, making the public—especially those facing economic hardship, social influence, and easy access—highly vulnerable. Online gambling not only violates the law but also poses serious social and economic consequences, such as addiction, debt, family breakdowns, and a rise in criminal behavior. Through a Community Service (PkM) activity conducted by lecturers from the Faculty of Law, Sunan Bonang University, Tuban, in Panyuran Village, legal and social education regarding the dangers and sanctions of online gambling was provided. This activity used participatory and descriptive approaches through lectures and interactive discussions. The results showed an increase in participants’ understanding of the mechanisms, impacts, and legal consequences of online gambling, while also fostering awareness to avoid engaging in such illegal practices. Preventive efforts such as continuous education and family-based supervision are expected to serve as strategic measures to minimize the spread of online gambling within society.